Comparison of robotic-assisted versus conventional laparoscopic surgery in colorectal cancer resection: a systemic review and meta-analysis of randomized controlled trials - Huang, Zhilong; Huang, Shibo; Huang, Yanping; Luo, Raoshan; Liang, Weiming (Frontiers in Oncology, 2023)
Introduction There is still controversy on whether or not robot-assisted colorectal surgery (RACS) have advantages over laparoscopic-assisted colorectal surgery(LACS).1 Zhilong Huang and Shibo Huang contributed equally to this study.The four databases(PubMed, Embase, Web of Science and Cochrane Library)were comprehensively searched for randomized controlled trials (RCTs) comparing the outcomes of RACS and LACS in the treatment of colorectal cancer from inception to 22 July 2023. Results Eleven RCTs were considered eligible for the meta-analysis.Compared with LACS,RACS has significantly longer operation time(MD=5.19,95%CI: 18.00,39.82， P<0.00001), but shorter hospital stay(MD=2.97,95%CI:−1.60,−0.33,P = 0.003),lower conversion rate ( RR=3.62,95%CI:0.40,0.76,P = 0.0003 ) , lower complication rate(RR=3.31,95%CI:0.64,0.89,P=0.0009),fewer blood loss ( MD=2.71,95%CI:−33.24,−5.35,P = 0.007 ) ,lower reoperation rate ( RR=2.12, 95%CI:0.33,0.96,P=0.03)and longer distal resection margin(MD=2.16, 95%CI:0.04,0.94， P = 0.03) .There was no significantly difference in harvested lymph nodes, the time of first flatus, the time of first defecation,the time of first resume diet,proximal resection margin,readmission rates, mortalities and CRM+ rates between two group. Conclusions our study indicated that RACS is a feasible and safe technique that can achieve better surgical efficacy compared with LACS in terms of short-term outcomes.